Synergistic action of the gut microbiota in environmental RNA interference in a leaf beetle - Xu, Letian (Microbiome, 2021)
BACKGROUND: RNA interference (RNAi) has emerged as an efficient tool to control insect pests. When insects ingest double-stranded RNAs (dsRNAs) targeted against essential genes, strong gene silencing and mortality can be induced. To exert their function, dsRNA molecules must pass through the insect’s gut and enter epithelial cells and/or the hemolymph. Gut bacteria are known to play multifarious roles in food digestion and nutrition, and confer protection against pathogens and parasites. Whether there is a cross talk between gut bacteria and ingested dsRNAs and whether the microbiome affects RNAi efficiency are unknown. RESULTS: Here, using a leaf beetle gut microbiota system, we investigated whether gut bacteria interact with dsRNA molecules and how the gut microbiota affects RNAi responses in insects. We first showed that the leaf beetle Plagiodera versicolora (Coleoptera) is highly susceptible to RNAi. We then demonstrated that ingestion of dsRNAs by non-axenic P. versicolora larvae results in (i) significantly accelerated mortality compared with axenic larvae, and (ii) overgrowth and dysbiosis of the gut microbiota. The latter may be caused by bacterial utilization of dsRNA degradation products. Furthermore, we found that Pseudomonas putida, a gut bacterium of P. versicolora, acts as major accelerator of the death of P. versicolora larvae by transitioning from commensal to pathogenic lifestyle. CONCLUSIONS: The present study illuminates the complex interplay between lethal dsRNA, the insect host, and its gut microbiota. The ingestion of dsRNA by the leaf beetle caused a dysbiosis of gut bacterial community, and the dsRNA degradation products by host insect preferentially promoted the growth of an entomopathogenic bacterium, which accelerated dsRNA lethality to the insect. Our findings reveal a synergistic role of the gut microbiota in dsRNA-induced mortality of pest insects, and provide new insights in the mechanisms of RNAi-based pest control. SUPPLEMENTARY INFORMATION: The online version contains supplementary material available at 10.1186/s40168-021-01066-1.